Virtuous violence hurting and killing to create, sustain, end, and honor social relationships - Fiske, Alan Page 1947-; Rai, Tage Shakti (Cambridge, [England] Cambridge University Press, 2015)
"What motivates violence? How can good and compassionate people hurt and kill others, or themselves? Why are people much more likely to kill or assault people they know well, rather than strangers? This provocative and radical book shows that people mostly commit violence because they genuinely feel that it is the morally right thing to do. In perpetrators' minds, violence may be the morally necessary and proper way to regulate social relationships according to cultural precepts, precedents and prototypes. These moral motivations apply equally to the violence of the heroes of the Iliad, to parents smacking their child, and many modern murders and everyday acts of violence. Virtuous Violence presents a wide-ranging exploration of violence across different cultures and historical eras, demonstrating how people feel obligated to violently create, sustain, end, and honor social relationships in order to make them right, according to morally motivated cultural ideals"-- Provided by publisher.
Machine generated contents note: The point; 1. Why are people violent?; 2. Violence is morally motivated to regulate social relationships; 3. Defense, punishment, and vengeance; 4. The right and obligation of parents, police, kings and Gods to violently enforce their authority; 5. Contests of violence: fighting for respect and solidarity; 6. Honor and shame; 7. War; 8. Violence to obey, honor and connect with the Gods; 9. On relational morality: what are its boundaries, what guides it and how is it computed?; 10. The prevailing wisdom; 11. Intimate partner violence; 12. Rape; 13. Making them one with us: initiation, clitoridectomy, infibulation, circumcision and castration; 14. Torture; 15. Homicide: he had it coming; 16. Ethnic violence and genocide; 17. Self-harm and suicide; 18. Violent bereavement; 19. Non-bodily violence: robbery; 20. The specific form of violence for constituting each relational model; 21. Why do people use violence to constitute their social relationships, rather than using some other medium?; 22. Metarelational models that inhibit or provide alternatives to violence; 23. How do we end violence?; 24. Evolutionary, philosophical, legal, psychological and research implications; The de;nouement.
Includes bibliographical references (pages 305-342) and index.
Keywords: Violence; Violence -- Moral and ethical aspects